Galen's Treatise 'Thrasybulus' and the dispute between 'Paidotribes' and Gymnastes' - Nieto Ibáñez, Jesús María (2003)
The revival of Greek sport in the second century AD coincides with the medical and philosophical critique of Galen against professional athletics, which has nega- tive effects on health and ethical and moral valúes. The treatise Thrasybulus sive utrum medicinae sit an gymnasticae hygieine is a doctrinal justification of the tech- nique of the gymnastes in contrast with that of the paidotribes.
Keywords: Deportes; Medicina